Requiem for the enslaved [compact disc] - Simon, Carlos, Jr., 1986-; Pavé, Marco (Decca, 2022)
American composer Carlos Simon presents a multi-genre work, Requiem for the Enslaved. This work is a musical tribute to commemorate the stories of 272 enslaved men, women and children sold in 1838 by Georgetown University. Described as a "rap opera," Carlos infuses his original compositions with African American spirituals and familiar Catholic liturgical melodies.